The Impact of Occupational Education on Obesity Prejudice of University Students - Ercan, Aydan; Akçil Ok, Mehtap; Altun, Simay (Progress in Nutrition, 2021)
Objective: The aim of this study was to investigate the obesity related prejudices and negative attitudes of university students who study in health and non-health fields. Subjective and Methods: This is a descriptive study conducted to determine the obesity prejudice levels of students studying in health and social fields. A total of 732 students (577 females, 155 males) of different faculties of a university participated in the study voluntarily. The Prejudice was measured with Obesity Prejudice Scale (OPS). Analysis of Variance and Covariance were used to investigate relationships between of OPS scores and factors. Results: A total of 732 students, 577 (78.8%) females and 155 (21.2%) males, participated in this study, which was conducted to determine obesity prejudices of university students. According to their mean OPS scores, 18.4% of the students were found to be unprejudiced, 55.1% prone to be prejudiced, and 26.5% prejudiced. The intragroup comparisons of mean OPS scores of health and social field students indicated that the differences between the prejudiced and the unprejudiced were statistically highly significant (p<0.0001). Conclusions: In order to prevent the development of internalized obesity prejudices emerging as a result of prejudices against obese individuals in the society and their stigmatization, this problem must be solved at an early age, especially during university education. It is necessary that state policies should be established to monitor the attitudes of individuals towards obesity, people should be educated and supervised on this subject, and that further research representing the society on this topic should be conducted.